Religion as a Determinant of Economic and Demographic Behavior in the United States - Evelyn Lilian Lehrer (Institute for the Study of Labor (IZA), 2004)
This paper critically reviews and synthesizes research on the role of religion on various aspects of the economic and demographic behavior of individuals and families in the United States, including the choice of marital partner, union formation and dissolution, fertility, female time allocation, education, wages, and wealth. Using a theoretical framework based on Gary Becker?s contributions to the economics of the family, religious affiliation is seen to affect these outcomes because it has an impact on the costs and benefits of many interrelated decisions that people make over the life cycle. In addition, for behaviors that pertain to married couple households, affiliation matters because it is a complementary trait within the context of marriage. Religiosity, another dimension of religion, also affects economic and demographic outcomes, partly because it accentuates differences by religious affiliation, partly because of the generally beneficial effects that religious involvement has on health and well-being.
Keywords: J2; J1; 330; religion; demography; marriage; female employment; education; fertility; Religion; Familienökonomik; Frauenerwerbstätigkeit; Fruchtbarkeit; Schätzung; Vereinigte Staaten